Uniformity and Diversity in the Enforcement of Arbitration Clauses in Canada - Saumier, Geneviève (2020)
Arbitration is well established in Canada. All jurisdictions have implemented the 1958 New York Convention, the UNCITRAL Model Law on Arbitration and equivalent legislation for domestic arbitration. This generally supportive legal landscape for arbitration is often at odds with access to justice for consumers. As a result, several jurisdictions in Canada have adopted legislation to guarantee consumers’ access to local courts, including through class actions, notwithstanding the inclusion of arbitration clauses in their contracts. The constitutional division of powers in Canada entitles each province to adopt its own policy, leading to diversity across the country with regard to the enforceability of arbitration clauses in consumer contracts. In this paper, the author examines the tension between general support for arbitration and differentiated treatment of consumer arbitration in Canada. To that end, the author examines relevant legislation in several provinces (including Quebec and Ontario) as well as recent jurisprudence from the Supreme Court of Canada (Dell Computer (2007), Telus (2011) and Wellman (2019)). The 2020 decision from the Supreme Court of Canada in Uber may signal a new openness toward extending protection to other vulnerable contracting parties such as employees.